Health risks of climate change in Australia: An umbrella review - Michael Tong; Enembe Okokon; Sotiris Vardoulakis (Elsevier, 2024)
Introduction: The impact of climate change on population health has been extensively studied in Australia, but no comprehensive review of the impact of climate change on health in Australia has been performed. This review summarizes the most up-to-date, high-level evidence exploring the health risks of climate change in Australia, identifies evidence gaps in the scientific literature, and lays the groundwork for an in-depth national climate change and health risk assessment in Australia. Methods: Electronic database PubMed was searched for systematic reviews of the impact of climate change on health outcomes in Australia. Narrative synthesis was conducted to summarize findings. Results: The most frequently reported climate change related risks in Australia were heat and bushfires, followed by floods and droughts, with a limited number of studies on cyclones and rising sea levels. The impacts on health included all-cause mortality and morbidity, heat-related illnesses, vector-, food- and water-borne diseases, negative mental health effects, cardiovascular, respiratory, and renal diseases, injuries and adverse birth outcomes. These impacts were unevenly distributed across Australia's geographical regions and population groups, particularly affecting young children, people with health conditions or disabilities, the elderly, and pregnant women. There were notable gaps concerning First Nations, culturally and linguistically diverse groups, ethnic minorities, and refugees in the context of climate change and health in Australia. Conclusions: Further research is needed to deepen our understanding of the associations between climate change and health outcomes in Australia, especially among disadvantaged communities and sensitive population groups. Future risk assessments using standardized methodologies to estimate exposure-response functions for specific health outcomes are warranted. At-risk populations need to be adequately supported by a national adaptation plan that will reduce their vulnerability to climate extremes and prevent adverse health impacts of climate change in Australia.